Lipid-biomarker-based sea surface temperature record offshore Tasmania over the last 23 million years - S. Hou; F. Lamprou; F. S. Hoem; M. R. N. Hadju; F. Sangiorgi; F. Peterse; P. K. Bijl (Climate of the Past, 2023)
The Neogene (23.04–2.58 Ma) is characterised by progressive buildup of ice volume and climate cooling in the Antarctic and the Northern Hemisphere. Heat and moisture delivery to Antarctica is, to a large extent, regulated by the strength of meridional temperature gradients. However, the evolution of the Southern Ocean frontal systems remains scarcely studied in the Neogene. Here, we present the first long-term continuous sea surface temperature (SST) record of the subtropical front area in the Southern Ocean at Ocean Drilling Program (ODP) Site 1168 off western Tasmania. This site is, at present, located near the subtropical front (STF), as it was during the Neogene, despite a 10 ∘ northward tectonic drift of Tasmania. We analysed glycerol dialkyl glycerol tetraethers (GDGTs – on 433 samples) and alkenones (on 163 samples) and reconstructed the paleotemperature evolution using TEX 86 and <msubsup> U 37 k ′ </msubsup> <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="5ec84048506428000d5895a3709a326f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-19-787-2023-ie00001.svg" width="18pt" height="18pt" src="cp-19-787-2023-ie00001.png"/></svg:svg> as two independent quantitative proxies. Both proxies indicate that Site 1168 experienced a temperate ∼ 25 ∘ C during the early Miocene (23–17 Ma), reaching ∼ 29 ∘ C during the mid-Miocene climatic optimum. The stepwise ∼ 10 ∘ C cooling (20–10 ∘ C) in the mid-to-late Miocene (12.5–5.0 Ma) is larger than that observed in records from lower and higher latitudes. From the Pliocene to modern (5.3–0 Ma), STF SST first plateaus at ∼ 15 ∘ C (3 Ma), then decreases to ∼ 6 ∘ C (1.3 Ma), and eventually increases to the modern levels around ∼ 16 ∘ C (0 Ma), with a higher variability of 5 ∘ compared to the Miocene. Our results imply that the latitudinal temperature gradient between the Pacific Equator and the STF during late Miocene cooling increased from 4 to 14 ∘ ...